Post COVID Guillain Barre Syndrome (GBS) in paediatric COVID unit of Dhaka Medical College: A case series - Akhter, Naznin; Shamsad, Iffat Ara; Islam, Rumana; Akter, Jesmin; Sultana, Kaniz; Yeasmin, Shamima; Anwar, Sayeeda (Journal of Dhaka Medical College, 2024)
SARS Cov-2 infection presents with mild respiratory illness but has evidence of multisystem involvement in little percentage, though the severity of infection is variable in children. Neurological manifestations may vary from headache, dizziness, olfactory or taste dysfunction to specific syndromes including meningoencephalitis, stroke, and acute transverse myelitis and Guillain- Barre syndrome (GBS). But there is little evidence worldwide about neurological complications of COVID-19 in children. Here we reporting five cases of post COVID-19 GBS with relevant literature review. J Dhaka Med Coll. 2022; 31(2) : 232-236